If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 9 = n + 6 Reorder the terms: 9 + 4n = n + 6 Reorder the terms: 9 + 4n = 6 + n Solving 9 + 4n = 6 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 9 + 4n + -1n = 6 + n + -1n Combine like terms: 4n + -1n = 3n 9 + 3n = 6 + n + -1n Combine like terms: n + -1n = 0 9 + 3n = 6 + 0 9 + 3n = 6 Add '-9' to each side of the equation. 9 + -9 + 3n = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 3n = 6 + -9 3n = 6 + -9 Combine like terms: 6 + -9 = -3 3n = -3 Divide each side by '3'. n = -1 Simplifying n = -1
| 2x+2=4x-5 | | 9c-4=2c+38 | | 49=17+w | | 2X+56= | | (5x+6)-(x^2+2x)= | | 22+6n=4+12n | | 1-2= | | x^4-4x^3+9x^2-20x+20=0 | | 10-14+6x-5(x+1)=-22+10 | | 0=-3x^2+6x^2+30x+24x+57x+120+228 | | 8x-4=2x^3-x^2 | | 3u^2-5u-3=25 | | 18ab+-6a+-7b+26ab+-7b= | | T^2-10t-20=19 | | 0=3x^2+111x+348 | | 6c-8ab+9c-10= | | -11x-10(-7x+35)=4 | | (4x^2-3)-(x^2+x+1)= | | 18x+12-10=-4 | | W^2-14w+24=0 | | -8(-8x-6x)=-6x-22 | | 20x^2-11x=-42 | | (6x^2+4x)-(3x^2-x)= | | x-8y=-48 | | 5*x+18=45 | | 8x+2y=96 | | 5x-6(-4x-5)=1 | | (-4x^2+x+7)-(-2x^2+x+2)= | | b-15=-23 | | 2m^2-11-1=-11m | | N^2-10n=-24 | | 2p+13=3-5 |